Relaxation lifetimes of plasmonically enhanced hybrid gold-carbon nanotubes systems. (1st June 2017) - Glaeske, M; Kumar, M; Bisswanger, T; Vaitiekenas, S; Soci, C; Narula, R; Bruno, A; Setaro, A
Abstract: Recently, we introduced a novel hybridization route for carbon nanotubes using gold nanoparticles, whose close proximity neatly enhances their radiative emission. Here we investigate the mechanisms behind the enhancement by monitoring the de-excitation dynamics of our π -hybrids through two-color pump-probe time-resolved spectroscopy. The de-excitation process reveals a fast component and a slow component. We find that the presence of gold prominently affects the fast processes, indicating a stronger influence of the gold nanoparticle on the intra-band non-radiative relaxation than on the inter-band recombination of the single-walled carbon nanotube. By evaluating the de-excitation times, we estimate the balance between near-field pumping and the faster metal-induced de-excitation contributions, proving the enhanced pumping to be the leading mechanism.